The Effect of Environmental Performance and Working Capital Management on Firm value with Profitability as an Intervening in the Textile Industry Sector - De Partho, Alviano; Mujanah, Siti; Alif Fianto, Achmad Yanu (International Journal of Economics (IJEC), 2025)
The integration of environmental sustainability and financial performance has become a growing concern in emerging economies, particularly within resource-intensive sectors such as the textile industry. This study investigates how environmental performance and working capital management affect firm profitability and firm value. It also examines the mediating role of profitability in these relationships. A quantitative research design was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The sample consisted of 15 textile companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2023. Data were collected from audited financial statements. Variables include environmental performance, working capital management, profitability (measured by ROA), and firm value (measured by Tobin's Q). The empirical results reveal that environmental performance has a negative and significant impact on profitability but positively influences firm value. Working capital management negatively impacts profitability but does not significantly influence firm value. Furthermore, profitability does not significantly affect firm value and does not mediate the relationship between the independent variables and firm value. The findings suggest that environmental initiatives can enhance firm value independently of short-term financial gains. In the textile industry context, non-financial performance, particularly environmental responsibility, is increasingly recognized by the market, even when profitability does not improve. These findings offer useful insights for corporate managers and policymakers aiming to promote sustainability without compromising market valuation